ROckfall risk MAnagement assessment: the RO.MA. approach - Mignelli, Claudia; Lo Russo, Stefano; Peila, Daniele (Natural hazards (Dordrecht), 2012)
The analysis of risk for vehicles and drivers as a result of rockfall on a road is relevant to design management in geotechnical engineering. This process is very complex due to the large number of parameters involved. In this paper, we discuss risk analysis and management procedures for roads subject to rockfall phenomena. To this aims, we are proposing a quantitative method (the RO.MA. approach). We developed an abacus to define the threshold values of acceptable rockfall risk for a given road. Rockfall risk is calculated using an Event Tree approach and compared with the abacus thresholds to evaluate road safety and the need for additional protective measures to reduce the risk to an acceptable level. The approach was successfully applied at a test site located in Bard, Aosta Valley, north-western Italy.